Metazoários parasitos dos lambaris Astyanax altiparanae Garutti & Britski, 2000, Astyanax bockmanni Vari & Castro, 2007 e astyanax fasciatus (Cuvier, 1819) (Characiformes: Characidae) coletados no rio Batalha, médio rio Tietê, SP, Brasil - Camargo, Aline de Almeida [UNESP] (2015)
The biodiversity of freshwater ecosystems have been threatened by environmental problems and the Batalha river that belongs to the Tietê-Batalha River Basin is an example environment that has suffered from several anthropogenic aggressions. In this sense, the study of parasitic fish fauna plays a key role, since it has several indicative of the conditions of ecosystems. Thus, the objective of this study was to diagnose qualitatively and quantitatively the parasite communities of Astyanax altiparanae, A. bockmanni and A. fasciatus from the Batalha river. In all, 125 fish were collected and recovered 1295 parasites belonging to four groups: Myxozoa (Henneguya sp.), Monogenea (Cacatuocotyle guaibensis, Characithecium sp., Diaphorocleidus kabatai, Diaphorocleidus sp.1, Diaphorocleidus sp.2, Diaphorocleidus sp.3 and Jainus hexops), Digenea (Austrodiplostomum compactum, Auriculostoma sp., Bacciger delvalleensis, Bellumcorpus majus, Clinostomum sp. and Diplostomidae gen. sp.) and Nematoda (Contracaecum sp., Cystidicoloides sp., Heliconema izecksohni, Philometroides caudata and Spiroxys sp.). For the analysis of seasonality, were collected 44 specimens of A. altiparanae in the dry period and 31 in rainy period. In both periods there was a higher prevalence of monogenetic. In the dry period three species of monogenetic showed positive correlations and the B. majus digenetic had negative correlation to the length of the hosts. In the rainy period only the parasite Diaphorocleidus sp.2 was positively correlated to the length of their hosts. All parasites except the B. majus digenetic had aggregated pattern for the dry period, in the period rainy all parasites showed an aggregated distribution pattern. How were collected only 19 specimens of A. bockmanni, were not performed statistical analyzes for this species of fish. Thirty-one A. fasciatus specimens were collected and the monogenetic accounted for the majority of parasites recovered...